Development of Augmented Reality Based Flashcard Learning Materials For Supply Chain Management at SMK Negeri 46 Jakarta - Marrina Azka Ahadiana; Henry Eryanto; Bayu Suhendry (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to develop an Augmented Reality (AR)-based Flashcard learning media for the Supply Chain Management material and to determine the feasibility, practicality, and effectiveness of the developed media. The study employed the Research and Development (R&D) method using the ADDIE model, which consists of the Analysis, Design, Development, Implementation, and Evaluation stages. Data were collected through validation questionnaires involving one material expert, one media expert, and one instructional design expert, pre-test and post-test, as well as student response questionnaires involving 72 Grade X Office Management students. The results showed that the developed Augmented Reality (AR)-based Flashcard learning media achieved an average feasibility score of 93.6%, categorized as “Very Feasible”, with expert validation scores of 93% from the material expert, 96% from the media expert, and 92% from the instructional design expert. In addition, the media obtained a practicality score of 94%, categorized as “Very Practical”, and an effectiveness result indicated by an N-Gain score of 0.74, categorized as “High Improvement”. These findings indicate that the developed learning media supports the learning process, enhances students’ understanding of Supply Chain Management concepts, and provides a more engaging and interactive learning experience. Therefore, the Augmented Reality (AR)-based Flashcard learning media is considered feasible, practical, and effective for use in Supply Chain Management learning at Phase E.